A Command for Laplace Regression. (July 2013) - Bottai, Matteo; Orsini, Nicola
We present the newlaplace command for estimating Laplace regression, which models quantiles of a possibly censored outcome variable given covariates. We illustratelaplace with an example from a clinical trial on survival in patients with metastatic renal carcinoma. We also report the results of a small simulation study.